Tinjauan Aksiologi dalam Filsafat Manajemen Pendidikan Islam Axiological Review in the Philosophy of Islamic Educational Management - Farhan Maulana, Ahmad; Ramadhan, Ganang; Hidayat, Wahyu; Supardi (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2023)
The integration of axiology, the philosophical study of values, within the framework of Islamic educational management is a critical exploration that seeks to align educational practices with the ethical principles inherent in Islamic philosophy. This paper delves into the significance of axiology in shaping the values, ethics, and moral foundation of educational management within an Islamic context. It explores the interplay between philosophical principles and the practical aspects of managing educational institutions in accordance with Islamic teachings. The study begins by elucidating the fundamental axiological tenets in Islamic philosophy, highlighting the centrality of values such as justice, compassion, integrity, and ethical conduct. It then examines how these values can be effectively incorporated into the managerial aspects of educational institutions, including curriculum development, leadership styles, and decision-making processes.Furthermore, the paper explores the challenges and opportunities that arise when applying axiological considerations to educational management within an Islamic framework. It investigates the potential conflicts with modern educational paradigms and the necessity of reconciling traditional Islamic values with contemporary pedagogical approaches. In conclusion, this research contributes to the ongoing discourse on the philosophy of Islamic educational management by emphasizing the importance of axiology in shaping an ethical and value-driven educational system. By synthesizing philosophical principles with practical management strategies, educators and administrators can foster an environment that not only imparts knowledge but also instills the core values integral to Islamic teachings. This approach aims to cultivate morally upright individuals who contribute positively to society while upholding the principles of Islamic philosophy in the realm of education.